Comparison of the effects of nicorandil, pinacidil and nitroglycerin on hypoxic and hypercapnic pulmonary vasoconstriction in the isolated perfused lung of rat. - Dumas, M. (1996)
1. The aims of this study were to compare in the rat isolated perfused lung preparation, the dilator actions of nicorandil, pinacidil and nitroglycerin on the hypoxic pulmonary pressure response with or without hypercapnic acidosis and to investigate the possible involvement of K channels and EDRF in these effects. 2. Isolated lungs from male Wistar rats (260-320 g) were ventilated with 21%O2 + 5%CO2 + 74%N2 (normoxia) or 5%CO2 + 95%N2 (hypoxia) and perfused with a salt solution supplemented with ficoll and gassed with 40%CO2 + 60%N2 to produce hypercapnic acidosis. Glibenclamide (1 microM), charybdotoxin (0.1 microM), NG-nitro-L-arginine methyl ester (L-NAME, 100 microM) and methylene blue (30 microM) were used to block KATP channels, KCa channels, EDRF synthesis and guanylate cyclase, respectively. 3. Hypoxic pressure response was significantly increased by hypercapnic acidosis (+115%, P < 0.001), L-NAME (+111%, P < 0.001), methylene blue (+100%, P < 0.05) but not by glibenclamide or charybdotoxin. In contrast none of these inhibitors affected the hypoxic hypercapnic acidosis response. 4. Nicorandil, pinacidil and nitroglycerin caused relaxation during the hypoxic pressure response and hypoxic hypercapnic acidosis response. Nicorandil was more potent in the latter. Glibenclamide inhibited the relaxant effects of nicorandil and pinacidil but not those of nitroglycerin during hypoxia alone. In contrast, glibenclamide inhibited the relaxant effects of the three drugs during hypoxia + hypercapnia. Charybdotoxin inhibited the relaxant effect of pinacidil during normocapnia and hypoxia but not those of nicorandil or nitroglycerin. Methylene blue inhibited partially the dilator response to pinacidil but did not modify the effects of nitroglycerin or nicorandil. 5. It is concluded that in the rat isolated lung preparation, EDRF limits hypoxic pulmonary vasoconstriction but not hypoxic vasoconstriction potentiated by hypercapnic acidosis, whereas KATP or KCa channels are not involved in either case. Nicorandil and pinacidil dilate pulmonary vessels mainly through KATP channels but the effects of pinacidil may also involve an additional mechanism of action through KCa channels. Finally it is suggested that nitroglycerin may partly exert its relaxant effects through KATP channels.